PENGARUH BERBAGI INFORMASI LOGISTIK, KAPABILITAS LOGISTIK, DAN KUALITAS INFORMASI TERHADAP KINERJA LOGISTIK - Sitaresmi Pribadi, Anya; Santosa, Wahyuningsih; Lunarindiah, Gatri; Kinanti Khasanah, Dewi (Penerbit Lafadz Jaya, 2026)
This study examines the direct effects of logistics information sharing, logistics capability, and information quality on logistics performance in manufacturing companies in Indonesia. A quantitative survey method was employed by distributing structured questionnaires to 168 respondents involved in logistics and supply chain activities. The data were analyzed using Structural Equation Modeling (SEM) with SPSS AMOS. The results show that logistics information sharing has a positive and significant effect on logistics performance, indicating that effective information exchange improves coordination and operational efficiency. Logistics capability also has a positive and significant effect on logistics performance, highlighting the importance of managing logistics resources and processes effectively. In addition, information quality positively and significantly affects logistics performance, emphasizing the role of accurate and timely information in logistics decision-making. The study concludes that logistics performance can be directly enhanced through effective information sharing, strong logistics capabilities, and high-quality information. These findings provide practical implications for manufacturing firms to improve logistics management and operational performance.